Jewish law and Italian local laws: from the Roman age to the 19th century - Colorni, Vittore (Studies in Jewish history and culture, 2025)
"From Roman times (when Jews first formed communities in Italy) throughout the 19th century (when Jews became emancipated individually but were deprived - as a group - of all their ancient autonomies), Jews remained tied to their separate judicial institutions. Administratively, Jewish communities sought control over their internal affairs (worship, charity, social welfare, schools, education, and their own communal rules) (administrative autonomy). Judicially, they sought recognition of their internal laws as applicable to their civic relations (regulatory autonomy), constantly striving to obtain from the State the authority to bring their community members to trial in their courts of law (judiciary autonomy)"--